Roma Youth's Perspective on an Inclusive Higher Education Community: A Hungarian Case Study - Aranka Varga; Gergely Horváth; Fanni Trendl (MDPI AG, 2024)
While the expansion of higher education increases access to higher qualifications, students from disadvantaged backgrounds are at an increased risk of dropping out. Research shows that student progression is more successful in inclusive higher education environments. The study focuses on the promotion of opportunities for Roma in higher education, contributing to the international discourse on this issue. A Hungarian higher education organization supporting young Roma people and students of socially disadvantaged backgrounds is presented, relying on the experiences of young people who have been members of this community over the past twenty years. The question is whether and how the inclusive characteristics of the organization are reflected in the recollections of our interviewees (N = 50) about the student society. The narrative content analysis of the interviews shows that the former students' entry into and time spent in the student society was embedded in a strong (peer and tutorial) social network, which framed and amplified the mentioned inclusive elements and forms of support of the organization. The inclusive approach and practices of the student society community played a key role in the mobility of Roma youth during their university years and beyond.